Correlation between benthic macroinvertebrate distribution and substrate composition in selected recreational rivers in Kelantan, Malaysia - Athirah Abas; Aweng Eh Rak; Syarifah Aisyah Syed Omar; Jayaraj V.K (UMT, 2018)
This study was carried out to determine the correlation between benthic macroinvertebrate and substrate composition in recreational rivers in Bukit Bakar, Jeram Pasu, and Lata Mengaji. Pebble count method and Surber net were used for substrates and benthic macroinvertebrate data collection, respectively. D50 of substrates compositions was calculated using the pebble count data and correlated with benthic macroinvertebrates compositions by using Pearson correlation. The highest D50 measured was at Lata Mengaji (Station 5) with 120.11mm and the lowest D50 at Jeram Pasu (Station 5) with 10.82mm. Therefore, results showed the different richness, composition, and distribution of families between the three sites. Athericidae, Chironomidae, Elmidae, Euphaeidae, Helodidae, Heptageniidae, Leptophlebiidae, Platystictidae, Psephenidae and Simuliidae show a significant difference between sites. However, among all of these families, only families Psephenidae and Elmidae had the highest correlation with D50 (p-value<0.05). This was concluded that the substrate size compositions and arrangement are factors that influence the benthic macroinvertebrate distribution in rivers.